POTRET KONTRIBUSI PAJAK HOTEL TERHADAP PAJAK DAERAH KOTA BANJARMASIN - Sugiarto, M.Hafiz; Yuliastina, Mellani; Isnawati, Isnawati; Maulina, Dessy; Rahman, Mizan Ikhlasul (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2023)
Taxes received from hotel is one regional or local-own income sources. There was a positive trend and significant rise of this tax revenue during 2018-2022, despite it declined in 2020 due to lockdown and low rate of hotel occupancy. This research dissects and analyzes the contribution of this so-called hotel tax revenue in Banjarmasin city. This research uses quantitative data and quantitative descriptive method. It discovered that the realization and target of this tax revenue fluctuated during 2018-2022 and has a minor contribution to regional income. In general, during these five years, the hotel tax revenue contributed less than 10 percent to the regional or local-own income.